Expressions of victory, Hellenism and power : the development of Campus Martius from the foundation of Rome to the end of the Republic - Hargis, Siobhán (Trinity College (Dublin, Ireland). Department of Classics, 2009)
The Campus Martius, Rome, was a flood plain to the north of the city of ancient Rome that was characterised by its extra-pomerial location and its overtly level, spacious, nature. The way in which the Campus Martius developed, from the foundation of Rome to the end of the Republic, is the focus of this thesis. In particular, the way in which military victory and its commemoration influenced the topography of the area, and how military victory was expressed through physical reminders of Greek culture, come in for particular attention.
Keywords: Classics, Ph.D.; Ph.D. Trinity College Dublin